Do College Youth Serve Others? How and Under Which Circumstances? Implications for Promoting Community Service. Issue 162 (December 2014) - Griffith, James; Thomas, Todd
Abstract : This chapter describes how data on the extent of community service among a national representative sample of young college students were associated with "supports, " including human, social, and cultural capital. This chapter helps fill missing information on estimates of the occurrence and persistence of community service, types of community service performed, and variables associated with performing such services.